ByzRev 07.2025.028: Maria Alessia Rossi, Visualizing Christ’s Miracles in Late Byzantium: Art, Theology, and Court Culture.: Cambridge: Cambridge University Press 2024. - Schroeder, Rossitza (The Byzantine Review, 2025)
Maria Alessia Rossi, Visualizing Christ’s Miracles in Late Byzantium: Art, Theology, and Court Culture. Cambridge: Cambridge University Press 2024. xxvii+337 pp., with illustrations. – ISBN 978-1-009-38762-0